The Dynamics, Challenges, and Strategic Opportunities of Solar Energy Development in the South Caucasus Countries - Markosyan, Meruzhan; Matevosyan, Elyanora; Markosyan, Ashot (Journal of Environmental Accounting and Management, 2026)
This study assesses the dynamics and opportunities of solar energy development in the three South Caucasus countries—Armenia, Azerbaijan, and Georgia—during 2018–2024. The region shows a clear upward trend in solar deployment, albeit at different speeds. Armenia expanded installed PV capacity from 17.3 MW to 485.4 MW (CAGR ≈ 74%/yr), Azerbaijan from 34.9 MW to 292.9 MW (CAGR ≈ 43%/yr; acceleration after 2022), and Georgia from 0.9 MW to 132.6 MW (CAGR ≈ 130%/yr, small-base effect). Growth is shaped by policy clarity, investment risk allocation, grid-integration readiness, and access to technology. The mixed-methods approach combines quantitative indicators (installed capacity, compound annual growth rates) with a structured qualitative review of policies and market rules. We complement country analysis with comparative views across former Soviet states and neighboring systems (Türkiye, Iran). Case notes (e.g., Masrik-1 in Armenia; Jabrayil/Shafag in Azerbaijan) illustrate utility-scale deployment and bring performance considerations (capacity factors, PPA/auction frameworks) into focus. Findings motivate a sequenced policy roadmap: regulatory stability, bankable PPAs, targeted grid upgrades, skills and supplier development, and pragmatic localization of components and services. Solar energy thus emerges not only as a clean electricity source but as an economic, environmental, and strategic lever for sustainable growth, energy security, and progress toward climate goals in the South Caucasus.